PENGELOLAAN PROGRAM KEAKSARAAN USAHA MANDIRI DALAM MENINGKATKAN KEMAMPUAN BERWIRAUSAHA WARGA BELAJAR - Ginanjar, Ahmad (PEDAGOGIA, 2016)
Issues addressed in this study is about the management of independent business literacy program in improving the ability of citizens to learn entrepreneurship. The purpose of this study was to describe: 1) Management of independent business literacy program in SKB Cianjur regency; 2) Ability to entrepreneurship learners in literacy programs, independent business in SKB Cianjur regency; 3) The factors supporting and literacy programs are independent business in SKB Cianjur regency. Respondents of this research 13 people. The method used in this research is descriptive method with qualitative research techniques. The results of this study found that: 1) The management of independent business literacy program in Cianjur regency SKB there are several stages: planning, implementation, and evaluation; 2) Ability to entrepreneurship learners in literacy programs, independent business in Cianjur district SKB that entrepreneurship skills in learners who take the program KUM seen from the characteristics of the learners themselves and how to take advantage of opportunities that exist. 3) The factors supporting and literacy programs are independent business in Cianjur district SKB is supporting factors in this program is on providing motivation to the participants given by tutors and managers so that people learn very enthusiastic about taking this KUM program.